Feature extraction and image processing - Nixon, Mark S.; Aguado, Alberto S.; Elsevier Science Publishers (Oxford ; Boston : Newnes, 2002)
Focusing on feature extraction while also covering issues and techniques such as image acquisition, sampling theory, point operations and low-level feature extraction, the authors have a clear and coherent approach that will appeal to a wide range of students and professionals. This is an ideal module text for courses in artificial intelligence, image processing and computer vision. It is an essential reading for engineers and academics working in this cutting-edge field. It is supported by free software on a companion website.
Front Cover; Feature Extraction and Image Processing; Copyright Page; Contents; Preface; Chapter 1. Introduction; Chapter 2. Images, sampling and frequency domain processing; Chapter 3. Basic image processing operations; Chapter 4. Low-level feature extraction (including edge detection); Chapter 5. Feature extraction by shape matching; Chapter 6. Flexible shape extraction (snakes and other techniques); Chapter 7. Object description; Chapter 8. Introduction to texture description, segmentation and classification; Chapter 9. Appendices; Index
Includes bibliographical references and index.
Keywords: Image processing; Software; Electronic books